The Effectiveness of a proposed program based on social Enhancement in the development of basic motor skills in children with simple mental disabilities that can be learned in kindergarten stage (Damascus University Journal of educational and Psychologyical sciences, 2021)
The current study aims at identifying the effectiveness of a proposed training program in improving basic motor skills in a sample of children with minor mental disabilities who have an IQ of /72-78/ Cogt-at cognitive abilities. The final study sample consisted of 8 children divided into experimental and control groups and 4 children per group. Their ages ranged between (6-4) years. The sample was selected within conditions that correspond to the nature of this study. The researcher used the basic motor skills scale in the study sample by means of an observation card designed by the researcher based on the scale. The validity and reliability of the tools of the study have been verified according to the scientific procedures followed by presenting them to a number of specialized referees. The researcher then built a proposed program and then applied it to the experimental group and it was presented to the referees themselves and took their suggestions.The most important results were:• There were no statistically significant differences at the mean level (0.05) between the mean grade of the control group and the experimental group on the basic motor skills scale after applying the program.   • There were statistically significant differences at the level of significance (0.05) between the average grade of the experimental group scores on the basic motor skills scale in the pre-post measurements due to the program.• There were no statistically significant differences at the level of significance (0.05) between the average grade of the experimental group scores on the basic motor skill scale in the post and delayed post-measurement.
Keywords: social reinforcement; basic motor skills; simple mental disability; children with simple mental disabilities who are able to learn.